2017
DOI: 10.1097/md.0000000000008410
|View full text |Cite
|
Sign up to set email alerts
|

Changes of cervical sagittal alignments during motions in patients with cervical kyphosis

Abstract: Changes of cervical sagittal alignment during motion in cervical kyphosis patients have never been published before. This study was to investigate the changes and provide a better reference for orthopedic treatment.Randomized double-blind repeat trial was carried out on 60 patients with cervical kyphosis. On standard position, hyper flexion, and hyper extension sagittal radiographs, the following measurements were made: the C2–7 vertebral body spatial alignment angle (∠A), C2–7 vertebral lower terminal lamina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We suggest it is due to both of these reasons. It has been verified that the most direct approach to correcting a cervical kyphosis is by applying a transverse load at the apex of the kyphosis 77) . This is consistent with using CBPs 'mirror image' approach, or the application of load vectors that are directly opposite to the spine misalignments 4,58) .…”
Section: Discussionmentioning
confidence: 99%
“…We suggest it is due to both of these reasons. It has been verified that the most direct approach to correcting a cervical kyphosis is by applying a transverse load at the apex of the kyphosis 77) . This is consistent with using CBPs 'mirror image' approach, or the application of load vectors that are directly opposite to the spine misalignments 4,58) .…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have suggested that the ROM at the vertex of cervical kyphosis will be reduced during exion-extension. [25] In this study, 80% of the 15 subjects with posterior convexity had a at C4-C5 segment at the apex of the posterior convexity, which resulted in inferior mobility in the corresponding segment in comparison to the normal group. Therefore, our research ndings may provide theoretical support for clinical practice, and attempting to intervene in changes in cervical curvature may restore physiological movement and delay cervical degeneration.…”
Section: Discussionmentioning
confidence: 66%
“…The following spinopelvic radiographic parameters were measured according to previously reported methods: [ 31 , 32 ] C7SVA, the distance from the C7 plumb line to a perpendicular line drawn from the posterosuperior corner of the S1; thoracic kyphosis (TK), the angle between the superior endplate of T5 and the inferior endplate of T12; thoracolumbar kyphosis (TLK), the angle between the superior endplate of T10 and the inferior endplate of L2; PT, the angle between the vertical and the line drawn through the sacral endplate midpoint to the femoral head axis; PI, the angle between the line drawn from the femoral head axis to the midpoint of the sacral endplate and the line perpendicular to the sacral endplate; LL, the angle between the superior endplate S1 and the superior endplate of L1. To measure SL, tangent lines were drawn along the inferior endplate of the superior vertebral body, and the superior endplate of the inferior vertebra at the level of interest, and the angle formed by the intersection of the two lines was SL [ 33 , 34 ]. Finally, PI − LL mismatch was also calculated, which was generally considered a predictor of ideal sagittal alignment following reconstructive surgery [ 4 , 35 ].…”
Section: Methodsmentioning
confidence: 99%